THE ABURAS HEURISTIC: A MODIFIED HEURISTIC FOR SCHEDULING UNRELATED PARALLEL MACHINE PROBLEMS - H.M. Aburas (South African Journal of Industrial Engineering, 2012)
ENGLISH ABSTRACT: Scheduling problems form an important class of decision-making problems where two types of decision have to be taken: allocation and sequencing. Scheduling is primarily considered with resource allocation; sequencing, however, is concerned with the order of jobs to be performed on the allocated resource (Sipper and Bulfin [8]). This paper proposes the use of a new heuristic called ABURAS, which is designed to minimize the makespan of an unrelated parallel machine scheduling problem. To evaluate the performance of the suggested heuristic, a real scheduling problem involving roof truss manufacturing at a major housing construction company is investigated. The ABURAS heuristic shows superiority in terms of reduced makespan over originally developed heuristics. AFRIKAANSE OPSOMMING: Skeduleringsvraagtukke vorm 'n belangrike versameling van besluitvormingsprobleme wat gekenmerk word deur toedeling en volgorde. Skedules hou verband met die toewysing van hulpbronne, terwyl sekwensie verband hou met volgorde. ’n Nuwe sogenaamde ABURAS-skeduleringsheuristiek word voorgehou vir praktyktoepassing. Die toepassingsprosedure word beskryf, en die heuristiek word toegepas by 'n onderneming wat dakkappe vervaardig. Die praktyktoepassing lewer bemoedigende resultate.